Cerebrospinal fluid tumour markers in patients treated for meningeal malignancy. Issue 2 (February 1991) - van Zanten, A P; Twijnstra, A; Ongerboer de Visser, B W; van Heerde, P; Hart, A A; Nooyen, W J
Abstract : The results of cerebrospinal fluid (CSF) biochemical markers were compared with conventional CSF cytology in patients treated for leptomeningeal metastases from extra cranial malignancies. For lumbar CSF, before treatment, no statistically significant difference of the probabilities of being positive was found between CSF cytology and a classification by linear discriminant analysis, based on patient's age, of beta-glucuronidase and beta 2-microglobulin. During treatment, classification by linear discriminant analysis was found more often positive than cytology. Possible mechanisms for this difference are discussed. For ventricular CSF a correlation was found between CSF cytology and beta-glucuronidase for solid tumours, and between CSF cytology and beta 2-microglobulin for haematological malignancies. Reference values for ventricular protein, CEA beta-glucuronidase and beta 2-microglobulin were obtained for cytological negative samples.